2011
DOI: 10.7589/0090-3558-47.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Bacterial Isolates From Sea Otters (Enhydra Lutris)

Abstract: ABSTRACT:Bacterial infections are an important cause of sea otter (Enhydra lutris) mortality, and some of these infections may originate from terrestrial and anthropogenic sources. Antimicrobials are an important therapeutic tool for management of bacterial infections in stranded sea otters and for prevention of infection following invasive procedures in free-ranging otters. In this study, susceptibility to commonly used antimicrobials was determined for 126 isolates of 15 bacterial species or groups from necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…It has been reported in southern sea otters that gram-positive and gram-negative bacteria account for 40% and 60% of isolates in necropsied, injured, and healthy rescued sea otters with the most common being Streptococcus spp., Corynebacterium, E. coli, and Vibrio spp. (Brownstein et al, 2011). In this study, six bacterial species had MIC 90 ≤ 0.25 lg/mL, three had MIC 90 ≤1 lg/mL, Vibrio parahaemolyticus MIC 90 1-4 lg/mL, and Klebsiella pneumoniae MIC 90 >8 lg/mL.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…It has been reported in southern sea otters that gram-positive and gram-negative bacteria account for 40% and 60% of isolates in necropsied, injured, and healthy rescued sea otters with the most common being Streptococcus spp., Corynebacterium, E. coli, and Vibrio spp. (Brownstein et al, 2011). In this study, six bacterial species had MIC 90 ≤ 0.25 lg/mL, three had MIC 90 ≤1 lg/mL, Vibrio parahaemolyticus MIC 90 1-4 lg/mL, and Klebsiella pneumoniae MIC 90 >8 lg/mL.…”
mentioning
confidence: 52%
“…, Corynebacterium, E. coli, and Vibrio spp. (Brownstein et al ., ). In this study, six bacterial species had MIC 90 ≤ 0.25 μg/mL, three had MIC 90 ≤1 μg/mL, Vibrio parahaemolyticus MIC 90 1–4 μg/mL, and Klebsiella pneumoniae MIC 90 >8 μg/mL.…”
Section: Noncompartmental Cefovecin Pharmacokinetic Indices For Adultmentioning
confidence: 97%
“…However, the clinical impact of disseminated Bartonella infection in sea otters was not clear. The observed high mortality due to VVE for northern sea otters from this region and confirmation of co-infection by Bartonella and other pathogenic bacteria in prior studies (Brownstein et al 2011, Carrasco et al 2014 suggests that Bartonella co-infections may be a contributor to the development of debilitating disease in northern sea otters.…”
Section: Discussionmentioning
confidence: 81%
“…Epidemiological studies have demonstrated that southern sea otters are at high risk for exposure to gastrointestinal protozoal pathogens and opportunistic bacteria in the coastal waters of central California (Miller et al 2008, Miller et al 2010a. Recent data also suggest that northern sea otters in Alaska have suffered increased exposure to and infection with pathogenic microorganisms that could make them more susceptible to predation and disease-associated mortality (Goldstein et al 2009, Goldstein et al 2011, Brownstein et al 2011.…”
mentioning
confidence: 99%
“…The river otter's oral flora may have included gram-negative organisms such as Escherichia coli, Salmonella sp. and Pasteurella multocida, 8 all of which could be resistant to ciprofloxacin. In a freshwater injury, consideration must also be given to Aeromonas sp., which may cause severe invasive infections and can carry ciprofloxacin resistance.…”
Section: River Otter Bitesmentioning
confidence: 99%